Mechanisms and therapeutic effectiveness of lactobacilli. Issue 3 (17th November 2015) - Di Cerbo, Alessandro; Palmieri, Beniamino; Aponte, Maria; Morales-Medina, Julio Cesar; Iannitti, Tommaso
Abstract : The gut microbiome is not a silent ecosystem but exerts several physiological and immunological functions. For many decades, lactobacilli have been used as an effective therapy for treatment of several pathological conditions displaying an overall positive safety profile. This review summarises the mechanisms and clinical evidence supporting therapeutic efficacy of lactobacilli. We searched Pubmed/Medline using the keyword ' Lactobacillus '. Selected papers from 1950 to 2015 were chosen on the basis of their content. Relevant clinical and experimental articles using lactobacilli as therapeutic agents have been included. Applications of lactobacilli include kidney support for renal insufficiency, pancreas health, management of metabolic imbalance, and cancer treatment and prevention. In vitro and in vivo investigations have shown that prolonged lactobacilli administration induces qualitative and quantitative modifications in the human gastrointestinal microbial ecosystem with encouraging perspectives in counteracting pathology-associated physiological and immunological changes. Few studies have highlighted the risk of translocation with subsequent sepsis and bacteraemia following probiotic administration but there is still a lack of investigations on the dose effect of these compounds. Great care is thus required in the choice of the proper Lactobacillus species, their genetic stability and the translocation risk, mainly related to inflammatory disease-induced gut mucosa enhanced permeability. Finally, we need to determine the adequate amount of bacteria to be delivered in order to achieve the best clinical efficacy decreasing the risk of side effects.